A Comparison of Achievement Gaps and Test‐Taker Characteristics on Computer‐Delivered and Paper‐Delivered Praxis I® Tests. Issue 2 (20th November 2014) - Steinberg, Jonathan; Brenneman, Meghan; Castellano, Karen; Lin, Peng; Miller, Susanne
Abstract : Test providers are increasingly moving toward exclusively administering assessments by computer. Computerized testing is becoming more desirable for test takers because of increased opportunities to test, faster turnaround of individual scores, or perhaps other factors, offering potential benefits for those who may be struggling to pass licensure examinations. This report extends previous research examining 4 years of paper‐based Praxis I ® test data to its corresponding computerized environment with these goals: (a) determine the extent to which achievement gaps exist on computer‐based (CB) Praxis I tests, (b) examine which test‐taker characteristics are most associated with mode, and (c) elicit opinions from previous Praxis I test takers to understand reasons why a particular testing mode was chosen. The results contribute to the literature about Praxis ® examinations and reinforce the need to understand their dynamics in the context of evaluating performance and participation gaps by demographic characteristics. Abstract : Report Number: ETS RR–14–35